Gender - COP29 Negotiation Updates - CGIAR Climate Change Impact Platform (CGIAR Climate Change Impact Platform, 2024)
Kenya’s submission on gender and climate change, supported by CGIAR, emphasizes the need for a GAP that promotes tangible, grassroots-level climate action, including mainstreaming gender in national policies, mapping gender-related climate vulnerabilities (in agriculture, water, and energy), and appointing focal points to promote gender-sensitive climate policies.